Santa-maria is a glial phagocytic receptor that acts with SIMU to recognize and engulf apoptotic neurons. - Hilu-Dadia, R.; Ghanem, A.; Vogelesang, S.; Ayoub, M.; Hakim-Mishnaevski, K.; Kurant, E. (Cell reports, 2025)
The elimination of superfluous neurons via apoptosis and subsequent glial phagocytosis is crucial for the development of the central nervous system (CNS). In Drosophila, two glial phagocytic receptors, six-microns-under (SIMU) and Draper, mediate the phagocytosis of apoptotic neurons during embryogenesis. However, in simu;draper double-mutant embryos, some apoptotic neurons are still engulfed by the glia, suggesting the involvement of additional receptors. Here, we discover the Drosophila CD36 homolog Santa-maria, a transmembrane receptor, which is specifically expressed in embryonic phagocytic glia and plays a major role in the recognition and engulfment steps of phagocytosis. Our data demonstrate that santa-maria genetically interacts with simu and draper, while the protein product binds apoptotic cells and physically interacts with the SIMU protein. Moreover, we reveal that triple knockout of genes for all three glial phagocytic receptors (i.e., simu, draper, and santa-maria) causes partial lethality, thus illuminating their role in development, particularly in the developing nervous system.